Hand gestures and hidden meanings: Exploring the semiotics of Balinese legong dance - Adnyani, Made Ayu Risma Dewi; Suarja, I Ketut; Budiarta, I Putu (Yayasan Mitra Persada Nusantara, 2025)
The primary aim of this study is to analyse the layers of symbolism embedded in the Legong dance of Bali. Rather than seeing Legong as simply “traditional dance,” this research investigates its deeper meanings—particularly how gestures, facial expressions, and costume are entwined with cultural myth and identity. The study also seeks to understand how these symbolic forms maintain cultural relevance for Balinese communities in contemporary times. Data collection involved observing Legong performances both live in Bali and through online recordings, ensuring a broad perspective on variations and consistencies. Semi-structured interviews were conducted with dancers, instructors, and cultural practitioners, focusing on how symbolism is taught, experienced, and understood. Informal participation in dance workshops provided an insider’s perspective on the embodied aspects of Legong symbolism. Detailed field notes were maintained, complemented by informal conversations that sometimes occurred in less formal settings like temple grounds. Every movement—from a delicate hand flick to intense, controlled eye movements—serves as a signifier within Balinese storytelling. Dancers are trained to communicate complex narratives about deities, conflict, courtship, and heroism through nonverbal cues. The use of ornate costumes, heavily jewelled headdresses, and vibrant fabrics reinforces the mythic quality of the characters portrayed. Even details like finger extensions and golden crowns contribute to the representation of supernatural or historical figures. Symbolism in Legong is sustained via a mixture of formal instruction and communal participation.